Whole-genome characterization of Shewanella algae strain SYT3 isolated from seawater reveals insight into hemolysis. (December 2018) - Wu, Zong-Yen; Ho, Shu-Peng; Cheng, Jan-Fang; Tung, Kwong-Chung; Hong, Yu-Kai; Chen, Shi-Yu; Menzer, Alexander; Chen, Ying-Ju; Huang, Yao-Ting; Liu, Po-Yu
Aim: To describe the genomic characteristics of seawater-borne hemolytic Shewanella algae and its resistance genes.Materials & methods: Whole genome sequence of S. algae SYT3 was determined using llumina MiSeq platform. Multiple-database-based analysis was performed to identify the genetic background of its hemolytic activity and the antibiotic resistance genes.Results: S. algae SYT3 possesses a homolog of the hly operon involved in the synthesis of hemolysin. We also identified candidate genes associated with resistance to β-lactam antibiotics ( bla OXA-55 ) and fluoroquinolone ( qnrA3 ).Conclusion: The study provides an insight into the hemolytic activity of S. algae . Our findings also suggested S. algae as a potential reservoir of antimicrobial resistance determinants.